PERBANDINGAN ANTARA INFORMASI SUHU PERMUKAAN LAUT DARI DATA SATELIT DENGAN HASIL PEMODELAN DI WPP NRI-716 - Komang Iwan Suniada (Environmental Research Center (PPLH) of Udayana University, 2016)
Sea Surface Temperature (SST) data and information recently become a valuableinformation since its association with the climate, oceanography condition and fisherieshave been discovered. Unfortunately, SST information using satellite imagery frequentlyconstrained by atmospheric cloud cover since satellite sensor disability to gather any landor ocean surface information through the cloud. Modeling data is very required to fill theblank data resulted from satellite imagery under cloudy condition. This study conducted atSulawesi Sea to North Halmahera which is included to Fisheries Managing Area (FMA)716, to find out the strength and direction relationship between SST model and SST satellite.Result indicates there is a strong and same direction relationship between SST model andSST satellite (r=0.704, n=1516) with 0.2C diferrence so that SST model can be used to fillor substitute the blank of SST satellite.